Innovative outpatient treatment for veterans and service members and their family members - Hoover, Gabrielle Groth; Teer, Andrew; Lento, René; Ward, Peter; Zakarian, Rebecca J.; Tinney, William; Sanders, Wesley; Echevarria, Katrina; Bonvie, Joseph; Dunford, Kathleen; Covitz, Jessica; Tanev, Kaloyan S. (Frontiers in Psychiatry, 2024)
In 2009, Massachusetts General Hospital and the Red Sox Foundation launched Home Base, a nonprofit dedicated to providing care to veterans, service members, and their loved ones who struggle with the invisible wounds of war free of charge. Significant needs exist for mental health services in each of these populations, and a need for innovative approaches to address shortcomings in existing treatment models. Three inventive components of our programming are highlighted herein: a Veteran Outreach Team, which helps to engage patients in care, programming, and services specifically for family members, and an intensive outpatient substance use treatment program. More than 4,000 patients, 3,031 veterans and service members, and 1,025 family members have engaged in treatment at Home Base. Patients were asked to complete post-treatment self-measures, including a satisfaction questionnaire via an electronic data collection system. The vast majority of individuals who engaged in our treatment model were satisfied with the care they received (>92%) and would refer their peers to the Home Base program (>75%). Data from 78 individuals who completed the dual diagnosis services demonstrated large effect sizes in reductions in alcohol use and comorbid mental health symptoms. These data suggest that novel components to the standard outpatient mental health model might provide substantive benefits for the patients served. While internal data is prone to a lack of generalizability, these additional offerings help ameliorate patients’ expressed shortcomings with existing models; present literature that describes the benefits that these additions provide is also reviewed. The lessons learned and limitations are discussed.